2011
DOI: 10.1007/s11276-011-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Converged multimedia services in emerging Web 2.0 session mobility scenarios

Abstract: The increasing request for converged multimedia services have motivated relevant standardization efforts, such as the Session Initiation Protocol (SIP) to support session control, mobility, and interoperability in all-IP next generation wireless networks. Notwithstanding the central role of SIP in novel converged multimedia, the potential of SIP-based service composition for the development of new classes of Web 2.0 services able to interoperate with existing HTTP-based services is still widely unexplored. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Latency in browser-based user-to-user interactions in our work was reported in [2]. A QoS-enabled SIP-based architectural scheme would be required in a bidirectional exchange of time-critical data between Web terminals.…”
Section: Qos-enabled Architectural Schemementioning
confidence: 94%
See 1 more Smart Citation
“…Latency in browser-based user-to-user interactions in our work was reported in [2]. A QoS-enabled SIP-based architectural scheme would be required in a bidirectional exchange of time-critical data between Web terminals.…”
Section: Qos-enabled Architectural Schemementioning
confidence: 94%
“…After that, the last part of the paper points out the wide potential area of application of the proposed solution, its easy application to these areas, and the future academic-/industry-oriented research directions that we will follow to extend our work in the next months. The comparison with other technologies in this article does not contain experimental evaluation in terms of performance and accuracy, another article [2] written by the authors reported the performance and accuracy of our work.…”
Section: Introductionmentioning
confidence: 99%
“…Other real-time communication solutions or native functionality execution like WebRTC, plugin based solutions [4] or implementation of a Web app with Googles NativeClient are not capable of reacting on external stimula, e.g. if no browser is running it is not possible to take an incoming communication request.…”
Section: Evaluation Of Our Solutionmentioning
confidence: 99%
“…There are many implementations of RTC among web browsers [3], [4], [5], [6], [7] and the WebRTC itself [8], [9], [10]. The standard signalling protocol for WebRTC is JavaScript Session Establishment Protocol (JSEP), however, Remote Object Access and Replication (ROAR) has also been used in some existing implementations.…”
Section: Introductionmentioning
confidence: 99%
“…Communication Service Aggregators (CSA) would help customers that run multiple clients on their phones save cost by running their services in cloud and offering them control via a browser. As earlier envisaged in [7], a click-to-call would not require an operator's voice network in order to setup a voice call,. VAS (Value Added Services) would be extended to web developers that can create value and solve problems for customers.…”
Section: Introductionmentioning
confidence: 99%